Production Analysis of Horizontal Wells in a Two-Region Composite Reservoir Considering Formation Damage - Li, Jingsong; Wang, Tao (Frontiers in Energy Research, 2022)
The horizontal well is extensively used to exploit oil in Bohai offshore oilfield, China. It has been proved by practice that formation damage always happens for production well. However, it is a challenging task to evaluate the formation damage for horizontal wells. In this paper, the flow model is established for horizontal well considering formation damage. The reservoir geometry is divided by two regions: inner region representing the region of formation damage and the outer region without damage. The finite element method is used to solve the flow model. The well production rate can be achieved by using the material balance method. For different scenarios such as when the horizontal well completely in the inner region or when the horizontal well passing through two regions, the effects of some key parameters such as damage radius, damage region permeability and well position on oil production rate and pressure distribution characteristics are analyzed. The results show that smaller damage radius, higher damage zone permeability and a horizontal well closer to or in greater contact with the outer region result in higher oil production rate and faster pressure drop propagation. The presented model and ob-tained results enrich production analysis of horizontal well in two-region composite reservoir considering formation damage which have significance on efficient offshore reservoir development.